Decision Making and Health Management for Cooperating UAS - Léchevin Nicolas; Rabbath Camille Alain (Safety And Reliability In Cooperating Unmanned Aerial Systems, 2010)
The following sections are included: Coordinated Rendezvous of UAS Formations Context Related work Multi-formations Models Cooperating UAS and urban environment Measurements Feasible paths Communication network UAS-threat encounters modeled as Markov decision processes Problem formulation Decision policies: perfect information Decision policies: partially known environment Information state estimation Rollout policy Computational load Design of CHM and decision making system Perfect information Partially known environment Cooperation Despite Information Flow Faults Context Impact of information flow fault on UAS decision policies Health state estimation Distributed computations of $\widetilde{W^{′}}_{k,P_{i},γ^{E},ν_{j}}$ Numerical Simulations Single target area and perfectly known environment Low-level health threat High-level health threat Sequence of targets and perfect knowledge of environment The case of perturbed MDPs Successive zones of surveillance in partially known environment Information flow faults Distributed and Parallel Implementation of Optimization Algorithms Context Architecture Distributed and parallel simulation environment Experiments